Impact of Driving Techniques on Fuel Consumption - Rievaj, Vladimír; Mokrickova, Lenka; Rievaj, Juraj (Communications - Scientific letters of the University of Zilina, 2016)
Climatologists constantly point to the change of the climate on Earth. They consider CO2 emissions to be one of the main causes of these changes. Transport is significant producer of the greenhouse gases. If one litre of gasoline is burnt, 2.5 kg of CO2 is released into environment. Incineration of one litre of oil means that the air gets 2.7 kg of CO2 [1]. Moreover, the air gets other pollutants, particularly nitrogen oxides NOx, unburned hydrocarbons, particulates. If we want to stop or delay the climate change, we should minimize production of the greenhouse gases. This objective could be implemented through legislation, designing of more efficient propulsion units, construction of infrastructure or using of alternative fuels. The easiest way is to minimize vehicle fuel consumption. This is dependent on driver and his driving techniques. The technical condition of the vehicle, route selection and the type of the vehicle are also significant [2]. We want to show the influence of the driving technique on the fuel consumption. Article describes four different driving techniques and their impact on the fuel consumption.